2011
DOI: 10.1155/2011/290132
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Epidermal Growth Factor Receptor Mutation of Nonsmall Cell Lung Cancer according to the Underlying Pulmonary Diseases

Abstract: Background. Although epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are effective in patients with nonsmall cell lung cancer with epidermal growth factor receptor (EGFR) mutation, EGFR-TKIs have a risk of inducing fatal interstitial lung disease (ILD). The selection of chemotherapy based on the EGFR mutation status is recommended, however, the frequency of EGFR mutation in patients with ILD and the efficacy and safety of EGFR-TKI in patients with ILD and EGFR mutation are unknown. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
3
17
0
1
Order By: Relevance
“…The incidence of EGFR mutations in the current cohort of Asian patients was 43.6%, most EGFR-mutated tumors harbored exon 19 or 21 mutations, accounting for 44.6% and 50% of all mutated tumors respectively. As expected, we found that EGFR mutations were more common among female patients and nonsmokers; this finding was consistent with previous results (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of EGFR mutations in the current cohort of Asian patients was 43.6%, most EGFR-mutated tumors harbored exon 19 or 21 mutations, accounting for 44.6% and 50% of all mutated tumors respectively. As expected, we found that EGFR mutations were more common among female patients and nonsmokers; this finding was consistent with previous results (24)(25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, some CT characteristics, especially those related to contrast enhancement of the lesion, which have not been previously evaluated for the purpose of finding prognostic factors for EGFR mutations, were found to have associations with EGFR mutation status. It is reported that the frequency of EGFR was low in patients with emphysema and fibrosis compared with the frequency of EGFR in patients without emphysema and fibrosis (25); however, the correlation between underlying lung diseases and EGFR mutation status in smokers with lung cancer has not been thoroughly investigated. We found that in smokers, those without severe emphysema or fibrosis have a higher possibility of developing EGFR-mutated tumors; this finding was in agreement with findings of a prior study (28).…”
Section: Thoracic Imaging: Epidermal Growth Factor Receptor Mutation mentioning
confidence: 99%
“…[1327] Overall mutation in the present study was 25.9% which falls in the range of 10-66%,[2028] reported in the published papers, irrespective of region and ethnicity. Studies from Korea,[18] Taiwan,[29] Japan,[30] and China,[7] have observed EGFR mutation rates as 24%, 50.5%, 26.3% and 38.1%, respectively. In the populations from Europe and America, frequency of EGFR mutation in lung adenocarcinoma has been observed as 17.3%,[12] 10.6%,[28] and 19%.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was reviewed and approved by the Ethics Committee of NTT Medical Center Tokyo. Patients were categorized into three groups based on the chest CT findings: those with normal lungs (except for the tumor), emphysema, or pulmonary fibrosis, as described previously (6)(7)(8). We collected the clinical and demographic data, including the gender, age, Eastern Cooperative Oncology Group Performance Status (PS), smoking history, clinical stage of SCLC, treatment, treatment-related toxicity and survival.…”
Section: Methodsmentioning
confidence: 99%